Pendekatan Dakwah Etis terhadap Kondisi Masyarakat Muslim Heterogen - Tajiri, Hajir (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2008)
Daâwah has two faces the existence of whichÂ depends to daâi. When daâwah is done by daâi having minimum competency in knowledge and faith, the performance of daâwah become fearing, in-productive, horrify and fearsome. On the contrary if daâwah is done by daâi havingÂ a lot of knowledge, strong faith, competency in using relevant method, so daâwahâs performanceÂ become good andÂ applicable to heterogeneous societies.